RECURRENT FEVER IN CHILDREN – DIAGNOSTIC APPROACH AND RED FLAGS FOR SERIOUS DISEASES - Dominika Julia Kozdroń; Michalina Weronika Nieścioruk; Dominika Raether; Adam Andrzejewski; Paulina Szczepańska; Jacek Kowalski; Dominika Dutkiewicz; Alia Echtay Yarbou; Rami Mallah (International Journal of Innovative Technologies in Social Science, 2026)
Recurrent fever in children represents a diagnostically challenging and clinically heterogeneous condition that extends beyond repeated exposure to common infections. While most febrile episodes in early childhood are self-limiting, a subset of children experiences recurrent episodes separated by periods of complete or near-complete well-being, necessitating careful evaluation to distinguish benign from serious underlying conditions. This review aims to synthesize the current state of knowledge regarding recurrent fever in children and to provide a clinically oriented analysis of the differential diagnosis. The specific objectives are to systematically characterize autoinflammatory, immunodeficiency-related, autoimmune, and oncologic causes; to outline a structured and evidence-based diagnostic approach; and to identify clinical red flags suggestive of a serious underlying pathology. Methods: This review is based on peer-reviewed literature on pediatric recurrent fever and periodic fever syndromes (references 1–27). Narrative and systematic reviews, clinical guidelines, and original studies were qualitatively synthesized with focus on etiology, immunopathogenesis, key clinical features, and diagnostic red flags. Results: Recurrent fever encompasses a broad spectrum of conditions, from benign periodic fever syndromes such as PFAPA to monogenic autoinflammatory diseases (FMF, TRAPS, MKD, CAPS), immunodeficiencies (CVID, cyclic neutropenia), autoimmune disorders (sJIA, SLE), and oncologic causes. Stepwise evaluation includes detailed history, physical examination, baseline and targeted laboratory testing, and genetic assessment when appropriate. Recognition of red flags—including growth retardation, persistent laboratory abnormalities, organomegaly, atypical fever patterns, severe systemic symptoms, and relevant family history—facilitates early identification of high-risk patients and guides targeted investigations. Conclusion: Early and structured assessment of children with recurrent fever, guided by clinical pattern recognition and red flags, is essential for accurate diagnosis, timely referral, and individualized management. Integration of immunopathogenic insights and practical diagnostic strategies enhances clinical decision-making and improves patient outcomes in potentially life-threatening conditions.